New ordinal names established by changes to the botanical code - Reveal, James L. (Phytotaxa, 2011)
At the 2011 Nomenclature Session held during the XVIII International Botanical Congress in Melbourne, Australia, it was decided that names above the rank of family treated under Art. 16.1 of the new International code of nomenclature for algae, fungi and plants, which came into effect on 30 July 2011, were not to be based on an included family but merely upon “a name of an included genus.” As a result a large number of effectively published suprafamilial names were validated for which the following are noted at this time. While the majority of these ordinal names are not in current use, a few are, namely Nepenthales, Osmundales, Polypodiales, Roridulales, Tamaricales, Taxales and Tropaeolales (Christenhusz et al. 2011a, 2011b, Reveal 2011; but see Reveal 2010 for all ordinal names published to that date, or for an up-to-date listing see www.plantsystematics.org/reveal/pbio/fam/allspgnames.html).